PEMANFAATAN ARTIFICIAL INTELLIGENCE UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK GURU DI SMKN 6 MUARO JAMBI - Nurmala Sari; Iwan Putra; Sudawan Supriadi; Sri Wahyuni; Dwi Rayana Siregar (Jurnal Pengabdian Masyarakat Khatulistiwa, 2025)
ABSTRACTIn the era of digital transformation, technological literacy, including the utilization of Artificial Intelligence (AI), has become an essential competency for teachers to enhance the quality of learning. AI-based technology not only strengthens learning effectiveness but also improves teachers’ work efficiency in various aspects. This training program at SMKN 6 Muaro Jambi aimed to enhance teachers’ pedagogical competence in designing lesson plans and learning evaluations based on the deep learning approach aligned with the principles of the Kurikulum Merdeka. The community service activity was conducted through participatory stages, including planning, problem identification, implementation with mentoring, and evaluation with reflection. The results revealed significant improvement in three key aspects: conceptual understanding of deep learning increased from 70.33 to 88.67 (a 24.17% rise), teachers’ ability to design lesson plans and reflective assessments based on deep learning improved from 70.53 to 86.77 (a 23.02% rise), and the ability to utilize AI tools increased from 72.89 to 91.26 (a 25.20% rise). These findings indicate that teachers are not merely users of AI technology but have evolved into designers and innovators of adaptive, creative, and contextually relevant learning experiences.Keywords: Deep Learning, Planning, Evaluation, Artificial Intelligence ABSTRAKDi era transformasi digital, literasi teknologi, termasuk pemanfaatan Artificial Intelligence (AI), menjadi kompetensi esensial yang harus dimiliki guru untuk meningkatkan mutu pembelajaran. Teknologi berbasis AI tidak hanya memperkuat efektivitas proses belajar, tetapi juga meningkatkan efisiensi kerja guru dalam berbagai aspek. Kegiatan pelatihan di SMKN 6 Muaro Jambi ini bertujuan untuk meningkatkan kompetensi pedagogik guru dalam merancang perencanaan dan evaluasi pembelajaran berbasis pendekatan deep learning yang selaras dengan tuntutan Kurikulum Merdeka. Program pengabdian kepada masyarakat ini dilaksanakan melalui beberapa tahapan partisipatif, meliputi perencanaan, identifikasi masalah, pelaksanaan dan pendampingan, serta evaluasi dan refleksi. Hasil kegiatan menunjukkan peningkatan signifikan pada tiga aspek utama: pemahaman konseptual tentang deep learning meningkat dari skor 70,33 menjadi 88,67 (naik 24,17%), kemampuan merancang perencanaan dan asesmen reflektif berbasis deep learning meningkat dari 70,53 menjadi 86,77 (naik 23,02%), dan kemampuan memanfaatkan AI tools meningkat dari 72,89 menjadi 91,26 (naik 25,20%). Temuan ini menunjukkan bahwa guru tidak hanya menjadi pengguna teknologi AI, tetapi juga berperan sebagai perancang pembelajaran yang adaptif, inovatif, dan relevan dengan kebutuhan zaman.Kata Kunci: Deep Learning, Perencanaan, Evaluasi, Artificial Intelligence